Design and Fabrication of a Low Cost Field Vane Shear Apparatus - Shahidur Rahman, Mohammad; Ullah, Ahad (Journal of Science and Technology, 2018)
The un-drained shear strength of soil is of great concern in many geotechnical engineering applications. The vane shear test is a simple, easy and popular type of in-situ shear test to the geotechnical engineers and geologists. However, it is not fairly appreciated by the academic personnel or field engineers as compared to the other shear strength test of soil. There are different types of field vane shear test apparatus existing in the market, but most of them are costly and have limited measuring capacity. The main objective of the research work was to develop a low cost field vane shear apparatus with higher measurement capacity using local materials and accessories. In this research work, a simple manually operated field vane shear apparatus was designed and fabricated. Four vane blades were welded to the vane shaft and a socket was added at the top. The most important component of the design apparatus is the torque wrench which is used to determine the torque both in clock and anti-clock wise direction. The torque value is then converted into the shear strength. The designed apparatus is suitable to determine the un-drained shear strength of soft to stiff clay soil up to 300 kPa. The performance of the device was tested directly in the crop field near Kumargaon area at Sylhet city. Average shear strength from in-situ test was found 49 kPa for medium to stiff clay. For the assessment of accuracy of the designed apparatus, undisturbed soil sample was collected from the same location of the field and then tested by laboratory vane apparatus according to ASTM D4648 and fairly similar result was observed. The instrument’s output repeatability was checked from the test data and the values were found quite satisfactory with a range of 2.68 to 5.87. The designed apparatus are about five times cheaper than the conventional apparatus available in the market.